Emergency extracorporeal shockwave lithotripsy as opposed to delayed shockwave lithotripsy for the treatment of acute renal colic due to obstructive ureteral stone: a prospective randomized trial. - Bucci, Stefano; Umari, Paolo; Rizzo, Michele; Pavan, Nicola; Liguori, Giovanni; Barbone, Fabio; Trombetta, Carlo (Minerva Urol Nefrol, 2018)
BACKGROUND: The aim of this study was to assess the efficacy of emergency extracorporeal shockwave lithotripsy (eSWL) as first-line treatment in patients with acute colic due to obstructive ureteral stone. METHODS: Seventy-four patients were randomized to emergency SWL within 12 hours (eSWL group) and deferred SWL later than 3 days (dSWL group). Follow-up included ultrasound, KUB (kidney-ureter-bladder) radiography and CT (computed tomography) scan at 24 hours, 7 days, 1 and 3 months from the treatment. When necessary, repeated SWL (re-SWL) or ureteroscopy (auxiliary-URS) was performed. Preoperative and postoperative data were compared and stone free rates (SFR) and efficiency quotients (EQ) were evaluated. Analyses were performed using SAS software. RESULTS: Complete data of 70 patients were collected. 36 underwent eSWL and 34 dSWL. The mean patient age was 48.7. Mean stone size was 9.8 mm (CI 95%: 8.9-10.8). 25 (35.7%) were proximal and 45 (64.3%) distal. Mean SWL energy was 19.2 kV (CI 95%: 18.5-19.9) and mean number of shocks was 2657 (CI 95%: 2513-2802). eSWL patients needs less auxiliary-URS than dSWL patients (13.9% vs. 44.1%, P=0.039) and less re-SWL sessions (8.3% vs. 32.4%, P=0.093). SFR at 24 hours was 52.8% and 11.8% (P<0.001) and the EQ at 3 months was 79.1% and 57.5% in the eSWL and dSWL group respectively. Patients from the dSWL group spent more time in the hospital (2.21 vs. 1.36 days, P=0.046) and complication rates between the two groups were similar. CONCLUSIONS: eSWL is a safe procedure and delivers high SFR even within 24 hours especially for <10 mm stones. It is able to reduce the number of auxiliary procedures and hospitalization.
Keywords: Aged; Calculi; Emergency Medical Services; Female; Humans; Length of Stay; Lithotripsy; Male; Middle Aged; Prospective Studies; Renal Colic; Time-to-Treatment; Tomography, X-Ray Computed; Ureteral Obstruction

Nutrient intakes in an Italian population of infants during the complementary feeding period. - Concina, Federica; Pani, Paola; Bravo, Giulia; Barbone, Fabio; Carletti, Claudia V; Knowles, Alessandra; Ronfani, Luca; Parpinel, Maria (Public Health Nutr, 2018)
OBJECTIVE: To describe the nutrient intakes of an Italian cohort of infants at 6, 9 and 12 months of age. DESIGN: Dietary data were collected using a food diary at three follow-ups (6, 9 and 12 months of age of infants). The infants' dietary data were used to estimate nutrient intakes using the Italian food composition database integrated with data from nutritional labels and the literature. The mean and standard deviation, median and interquartile range, minimum and maximum, and 5th, 25th, 75th and 95th percentiles were calculated for the daily intake of twenty-eight nutrients, with sex differences evaluated using parametric/non-parametric statistical methods. SETTING: A prospective population-based birth cohort.SubjectInfants (n 400) living in the urban area of Trieste (Italy). RESULTS: The sex distribution was fairly balanced at each follow-up. The mean daily intakes of energy and the other twenty-seven nutrients considered were greater in males at all follow-ups. In particular, a significant statistical difference was observed in higher male consumption of cholesterol at 9 months and in energy and carbohydrate intakes at 12 months (P < 0·05). The mean daily intake of proteins was greater than that recommended by the Italian Dietary Reference Values at all follow-ups. CONCLUSIONS: These preliminary results provide a useful basis for understanding the nutrient intake patterns of infants in this area of Italy during the first year of life.

Circulating osteoprotegerin is associated with chronic kidney disease in hypertensive patients. - Bernardi, Stella; Toffoli, Barbara; Bossi, Fleur; Candido, Riccardo; Stenner, Elisabetta; Carretta, Renzo; Barbone, Fabio; Fabris, Bruno (BMC Nephrol, 2017)
BACKGROUND: Osteoprotegerin (OPG) is a glycoprotein that plays an important regulatory role in the skeletal, vascular, and immune system. It has been shown that OPG predicts chronic kidney disease (CKD) in diabetic patients. We hypothesized that OPG could be a risk marker of CKD development also in non-diabetic hypertensive patients. METHODS: A case-control study was carried out to measure circulating OPG levels in 42 hypertensive patients with CKD and in 141 hypertensive patients without CKD. A potential relationship between OPG and the presence of CKD was investigated and a receiver-operating characteristic (ROC) curve was designed thereafter to identify a cut-off value of OPG that best explained the presence of CKD. Secondly, to evaluate whether OPG increase could affect the kidney, 18 C57BL/6J mice were randomized to be treated with saline or recombinant OPG every 3 weeks for 12 weeks. RESULTS: Circulating OPG levels were significantly higher in hypertensive patients with CKD, and there was a significant inverse association between OPG and renal function, that was independent from other variables. ROC analysis showed that OPG levels had a high statistically predictive value on CKD in hypertensive patients, which was greater than that of hypertension. The OPG best cut-off value associated with CKD was 1109.19 ng/L. In the experimental study, OPG delivery significantly increased the gene expression of pro-inflammatory and pro-fibrotic mediators, as well as the glomerular nitrosylation of proteins. CONCLUSIONS: This study shows that OPG is associated with CKD in hypertensive patients, where it might have a higher predictive value than that of hypertension for CKD development. Secondly, we found that OPG delivery significantly increased the expression of molecular pathways involved in kidney damage. Further longitudinal studies are needed not only to evaluate whether OPG predicts CKD development but also to clarify whether OPG should be considered a risk factor for CKD.
Keywords: Aged; Animals; Biomarkers; Case-Control Studies; Female; Follow-Up Studies; Humans; Hypertension; Male; Mice; Mice, Inbred C57BL; Middle Aged; Osteoprotegerin; Random Allocation; Renal Insufficiency, Chronic

CYP3A genes and the association between prenatal methylmercury exposure and neurodevelopment. - Llop, Sabrina; Tran, Van; Ballester, Ferran; Barbone, Fabio; Sofianou-Katsoulis, Aikaterini; Sunyer, Jordi; Engström, Karin; Alhamdow, Ayman; Love, Tanzy M; Watson, Gene E; Bustamante, Mariona; Murcia, Mario; et al. (Environ Int, 2017)
BACKGROUND: Results on the association between prenatal exposure to methylmercury (MeHg) and child neuropsychological development are heterogeneous. Underlying genetic differences across study populations could contribute to this varied response to MeHg. Studies in Drosophila have identified the cytochrome p450 3A (CYP3A) family as candidate MeHg susceptibility genes. OBJECTIVES: We evaluated whether genetic variation in CYP3A genes influences the association between prenatal exposure to MeHg and child neuropsychological development. METHODS: The study population included 2639 children from three birth cohort studies: two subcohorts in Seychelles (SCDS) (n=1160, 20 and 30months of age, studied during the years 2001-2012), two subcohorts from Spain (INMA) (n=625, 14months of age, 2003-2009), and two subcohorts from Italy and Greece (PHIME) (n=854, 18months of age, 2006-2011). Total mercury, as a surrogate of MeHg, was analyzed in maternal hair and/or cord blood samples. Neuropsychological development was evaluated using Bayley Scales of Infant Development (BSID). Three functional polymorphisms in the CYP3A family were analyzed: rs2257401 (CYP3A7), rs776746 (CYP3A5), and rs2740574 (CYP3A4). RESULTS: There was no association between CYP3A polymorphisms and cord mercury concentrations. The scores for the BSID mental scale improved with increasing cord blood mercury concentrations for carriers of the most active alleles (β[95% CI]:=2.9[1.53,4.27] for CYP3A7 rs2257401 GG+GC, 2.51[1.04,3.98] for CYP3A5 rs776746 AA+AG and 2.31[0.12,4.50] for CYP3A4 rs2740574 GG+AG). This association was near the null for CYP3A7 CC, CYP3A5 GG and CYP3A4 AA genotypes. The interaction between the CYP3A genes and total mercury was significant (p<0.05) in European cohorts only. CONCLUSIONS: Our results suggest that the polymorphisms in CYP3A genes may modify the response to dietary MeHg exposure during early life development.
Keywords: Adult; Child Development; Child, Preschool; Cohort Studies; Cytochrome P-450 CYP3A; Female; Fetal Blood; Genotype; Greece; Humans; Infant; Italy; Male; Mercury; Methylmercury Compounds; Neurodevelopmental Disorders; Neuropsychological Tests; Polymorphism, Genetic; Pregnancy; Prenatal Exposure Delayed Effects; Seychelles; Spain

Incidence and Estimated Prevalence of Endometriosis and Adenomyosis in Northeast Italy: A Data Linkage Study. - Morassutto, Caterina; Monasta, Lorenzo; Ricci, Giuseppe; Barbone, Fabio; Ronfani, Luca (PLoS One, 2016)
Despite being quite frequent and having serious implications in terms of symptomatology and fertility, data on incidence and prevalence of endometriosis and adenomyosis following gold standard definitions are dramatically lacking. The average time from onset of symptoms to diagnosis in industrialized countries still ranges from five to ten years. Using the regional centralized data linkage system, we calculated incidence and prevalence of endometriosis and adenomyosis in the female population of Friuli Venezia Giulia region, Italy, for the years 2011-2013. Cases were defined as new diagnoses from hospital discharge records, following procedures allowing direct visualization for endometriosis and hysterectomy for adenomyosis, with or without histological confirmation. Diagnoses were considered "new" after verifying women had not been diagnosed in the previous ten years. Incidence of endometriosis and adenomyosis in women aged 15-50 years is 0.14%. Prevalence, estimated from incidence, is 2.00%. Adenomyosis, representing 28% of all diagnoses, becomes increasingly prevalent after the age of 50 years. Our results shows how the study of both endometriosis and adenomyosis should not be limited to women of premenopausal age. Further efforts are needed to sensitize women and health professional, and to find new data linkage possibilities to identify undiagnosed cases.

Osteoprotegerin increases in metabolic syndrome and promotes adipose tissue proinflammatory changes. - Bernardi, Stella; Fabris, Bruno; Thomas, Merlin; Toffoli, Barbara; Tikellis, Christos; Candido, Riccardo; Catena, Cristiana; Mulatero, Paolo; Barbone, Fabio; Radillo, Oriano; Zauli, Giorgio; Secchiero, Paola (Mol Cell Endocrinol, 2014)
BACKGROUND: Inflammation is believed to link obesity to insulin resistance, as in the setting of metabolic syndrome (MetS). Osteoprotegerin (OPG) is a soluble protein that seems to exert proatherogenic and prodiabetogenic effects. This study aims at determining OPG levels in MetS and whether OPG might contribute to MetS development and progression. METHODOLOGY/PRINCIPAL FINDINGS: Circulating OPG was measured in 46 patients with MetS and 63 controls, and was found significantly elevated in those with MetS. In addition, circulating and tissue OPG was significantly increased in high-fat diet (HFD) fed C57BL6 mice, which is one of the animal models for the study of MetS. To evaluate the consequences of OPG elevation, we delivered this protein to C57BL6 mice, finding that it promoted systemic and adipose tissue proinflammatory changes in association with metabolic abnormalities. CONCLUSIONS/SIGNIFICANCE: These data suggest that OPG may trigger adipose tissue proinflammatory changes in MetS/HFD-induced obesity.
Keywords: Adipose Tissue; Adult; Animals; Blood Glucose; Body Mass Index; C-Reactive Protein; Case-Control Studies; Cholesterol, HDL; Cholesterol, LDL; Diet, High-Fat; Female; Humans; Inflammation; Insulin; Insulin Resistance; Male; Metabolic Syndrome X; Mice; Mice, Inbred C57BL; Middle Aged; Obesity; Osteoprotegerin; Triglycerides